Soil problems in housing development projects: a legal analysis - Zamalik, Maryam Nabilah (The Mattingley Publishing Co., Inc., 2020)
Soil problems in housing projects are potentially hazardous to house purchasers,neighborhood residents as well as the public safety with consequential economic loss. Although there are guidelines and policies supporting the housing industry in Malaysia, the occurrence of problematic soils in housing projects still persists as little regulatory control on housing project being carried out. In addition, there is no currently specific regulation exists in Malaysia to govern soil fitness in housing development projects.Soil problems are natural hazards that include land slide, soil erosion, unsuitable site conditions, or instability land location that triggering building collapses and failures to the detriment of house purchaser and stakeholders. In essence, this writing provides description on the study of legal issues pertaining to soil problems in housing projects that occur right from the outset of the development till the completion of the housing projects. These problems are diverse and the lack of enforcement in the legal framework is the primary factor. This paper aims to review the laws governing problematic soils whether the provisions had been incorporated in Street Drainage Building Act 1974, Town Country Planning Act 1976, Uniform Building By-Law 1984, and National Land Code 1965.Similarly, other related acts that govern the soil problem will be examined too. By using legal research method, the study adopts case law where judicial decision being the primary source to highlight the legal problems in relation to problematic soils. The study also includes interview that forms as part of the research validity. It is timely that these legislation's need to clearly define the responsibility and liability of stakeholders and the local authority which this stand as loopholes in the law. This issue of soil problems is not resolved, and the public complaints are mounting which if not well addressed, it is anticipated that the housing industry will experience future catastrophic losses. It is always the house purchasers who become victims and residents living in the neighborhood might be affected too.